2022
DOI: 10.7717/peerj.13865
|View full text |Cite
|
Sign up to set email alerts
|

Semi-field evaluation of human landing catches versus human double net trap for estimating human biting rate of Anopheles minimus and Anopheles harrisoni in Thailand

Abstract: Background Whilst the human landing catch (HLC) technique is considered the ‘gold standard’ for estimating human-biting rates, it is labor-intensive and fraught with potential risk of exposure to infectious mosquito bites. This study evaluated the feasibility and performance of an alternative method, the human double net trap (HDNT) relative to HLC for monitoring host-seeking malaria vectors of the Anopheles minimus complex in a semi-field system (SFS). M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 62 publications
(92 reference statements)
0
5
0
Order By: Relevance
“…KU’s An. minimus laboratory (L) strain is originally from Rong Klang district, Prae province, Thailand, and has been reared at KU’s insectary for the purpose of SFS studies since 1993 [ 22 ]. For this study, female An.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…KU’s An. minimus laboratory (L) strain is originally from Rong Klang district, Prae province, Thailand, and has been reared at KU’s insectary for the purpose of SFS studies since 1993 [ 22 ]. For this study, female An.…”
Section: Methodsmentioning
confidence: 99%
“…Also, a field study in Malaysia for evaluating the trapping densities of the HDN (and other trap types) compared to the HLC found that the HDN collected significantly less Anopheles than the HLC [ 21 ]. Further, in Thailand, a recent SFS evaluation of the performance of the HDN compared to the HLC for monitoring Anopheles minimus complex showed that the HDN captured significantly fewer mosquitoes than the HLC, indicating that the HDN might not be a suitable alternative to the HLC in this context [ 22 ]. Given this conflicting body of evidence on the suitability of the HDN as an alternative to the HLC, additional HDN evaluations are needed to help bring clarity around use of the HDN as a trap alternative to the HLC.…”
Section: Introductionmentioning
confidence: 99%
“…ITCs primarily protect humans from mosquito bites through contact irritancy (also referred to as contact excito-repellency), some short-range non-contact excitorepellency, feeding inhibition, and mortality [15][16][17]. VPSRs have been extensively evaluated in Africa [18][19][20][21][22][23][24] and increasingly in Southeast Asia [25][26][27][28][29]. ITCs, treated with pyrethroids, have been widely evaluated and show promise for their use against Anopheles biting amongst mobile populations and military/ranger personnel [30][31][32][33].…”
Section: Introductionmentioning
confidence: 99%
“…Here, mosquitoes are captured from the lower limbs of a human volunteer as they land, but before they bite. HLC is a direct measurement of human-vector contact that has not been reproduced accurately using traps [3][4][5], but it has disadvantages especially with wild-field mosquitoes, as pathogen transmission could occur [5]. There is some experimental evidence that HLCs provide a reasonable proxy of human biting [6,7].…”
Section: Introductionmentioning
confidence: 99%